The Legal Aspects of Privatization in Electricity Business Sector - Hidayatulloh, Hidayatulloh; Erdős, Éva (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Privatization is a crucial issue for third-world countries such as Indonesia. In the electricity sector, which is the lifeblood of the community, the involvement of the private sector is a crucial concern. Two judicial reviews of the electricity law in 2003 and 2015 proved the significant issue of privatization in electricity. This study analyzes how the state regulates the privatization policy of the electricity sector in Indonesia. This study, a normative or doctrinal legal research model, explores electricity regulations and doctrines such as Laws Number 20 of 2002 and Number 30 of 2009, Law Number 11 of 2020 on Job Creation, and two decisions of the Constitutional Court number 001-021-022/PUU-I/2003 and 111/PUU-XIII/2015. In conclusion, this study explains that Indonesia allows the privatization of the electricity sector throughout the role of private companies is still under state control. Privatization, which is a reduction in the role of the state and an increase in the role of the private sector, has been well implemented by state-owned enterprises, including the electricity sector. Both decisions of the Constitutional Court emphasize the strong role of the state and become the majority in controlling the electricity business, but do not reject the role of the private sector. Furthermore, state-owned enterprises have a top priority as a provider of electricity for the community.